UJI AKTIVITAS ANTIOKSIDAN MENGGUNAKAN RADIKAL 1,1-DIFENIL-2- PIKRILHIDRAZIL DAN PENETAPAN KANDUNGAN FENOLIK TOTAL FRAKSI ETIL ASETAT EKSTRAK ETANOL BUAH ANGGUR BALI (Vitis vinifera L.) - Mikhael Gustandy; C.J. Soegihardjo (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2013)
Abstract: This research was conducted to determine the antioxidant activity of ethyl acetatfraction of extract of Balinesse grape (Vitis vinifera L.) using free radical and determine the totalphenolic content. Balinesse grape was extracted with ethanol and then fractionated using ethylacetate. Free radical scavenging activity was tested by measuring the DPPH radical scavengingactivity. Total phenolic content was determined using the Folin-Ciocalteau method measured theconcentration of phenolic content in gallic acid total equivalents using unit's mg/g. The mean IC50value for DPPH radical scavenging activity of the ethyl acetat fraction of ethanolic extract ofBalinesse grape was found to be 36.55 0.09 g/mL. The phenolic content was ranging from 3.23 0.02 mg gallic acid equivalents per gram of ethyl acetat fraction of ethanolic extract ofBalinesse grape.Keywords: antioxidants, Balinesse grape (Vitis vinifera L.), fraction of ethyl acetat, DPPH, totalphenolic content.